Olmesartan‐associated enteropathy: results of a national survey. Issue 9 (9th September 2014) - Marthey, L.; Cadiot, G.; Seksik, P.; Pouderoux, P.; Lacroute, J.; Skinazi, F.; Mesnard, B.; Chayvialle, J. A.; Savoye, G.; Druez, A.; Parlier, D.; Abitbol, V.; et al.
Summary Background Recently, a new enteropathy has been described: olmesartan‐associated enteropathy. However, the association has been questioned: a phase 3 trial and a cohort study found no association between gastrointestinal events and olmesartan. Aim To collect French cases of sartan‐associated enteropathy to describe further this entity, confirm or refute causality, and determine if the association exists with other sartans. Methods French gastroenterologists were invited to report cases of sartan‐associated enteropathy and collect clinical, biological and histological data. Patients with diarrhoea and histological duodenal abnormalities were included. Results Thirty‐six patients with olmesartan‐associated enteropathy were reported, including 32 with villous atrophy and four without. There was only one patient with irbesartan‐associated enteropathy. None of the patients died. Patients with villous atrophy had diarrhoea, vomiting, renal failure, hypokalaemia, body weight loss and hypoalbuminaemia. Thirty‐one patients were hospitalised; four required intensive care. Anti‐transglutaminase and anti‐enterocyte antibodies were negative; anti‐nuclear antibodies were positive (9/11). Endoscopic duodenal biopsies showed villous atrophy (32/32) and polyclonal intra‐epithelial CD3+CD8+ lymphocytosis (11/11). Exactly, 14/15 patients responded to steroids and/or immunosuppressants, prescribed because of suspected autoimmune enteropathy. Ten olmesartan interruptions were followed by reintroductions before steroids or immunosuppressants. Interruptions were followed by remissions (9/10), but reintroductions were followed by relapses (9/9). Twenty‐nine patients were in remission since olmesartan interruption, including 26 without immunosuppressants. Patients with normal villi had similar clinical characteristics, but mild histological abnormalities (intra‐epithelial lymphocytosis and lamina propria lymphocytic infiltration). Conclusions Olmesartan causes a severe and immune‐mediated enteropathy, with or without villous atrophy. Enteropathy associated with other sartans seems to be very rare.